2020
DOI: 10.1002/cbic.202000674
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Side‐Chain NMR Relaxation Data to Derive Structural and Dynamical Information on Proteins: A Case Study Using Hen Lysozyme

Abstract: Values of S2CH and S2NH order parameters derived from NMR relaxation measurements on proteins cannot be used straightforwardly to determine protein structure because they cannot be related to a single protein structure, but are defined in terms of an average over a conformational ensemble. Molecular dynamics simulation can generate a conformational ensemble and thus can be used to restrain S2CH and S2NH order parameters towards experimentally derived target values S2CH (exp) and S2NH (exp). Application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Under solution conditions, any hydrogen bonds between molecules in different trimers will clearly be missing. In addition, any intramolecular or inter-monomer hydrogen bonds involving side chain groups on the surface of the protein are expected to be fluctuating with short lifetimes [ 30 ]. Consequently, the quaternary structure of the trimer is likely to be an ensemble of conformers, rather than any one of the different structures seen in crystals predominating in solution.…”
Section: Resultsmentioning
confidence: 99%
“…Under solution conditions, any hydrogen bonds between molecules in different trimers will clearly be missing. In addition, any intramolecular or inter-monomer hydrogen bonds involving side chain groups on the surface of the protein are expected to be fluctuating with short lifetimes [ 30 ]. Consequently, the quaternary structure of the trimer is likely to be an ensemble of conformers, rather than any one of the different structures seen in crystals predominating in solution.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a possible force-field deficiency hampering the agreement with experiment can be redressed using this restraining technique. In this way configurational ensembles consistent with NMR data can be generated allowing a structural interpretation of experimental observations [14,15]. We will demonstrate the use of time-averaged order parameters by means of the third IgG-binding domain of Protein G (GB3), which is a small 56-residue protein.…”
Section: Tutorial 1: S 2 Order Parameter Restrainingmentioning
confidence: 99%
“…of r XY is essentially constant over time and thus equal to its effective value r eff XY . The set of 79 experimentally derived S 2 values (Buck et al 1995;Moorman et al 2012) together with the S 2 values calculated from the five MD simulations started from the 2VB1 X-ray crystal structure (Smith et al 2020) can be found in Supporting Information, Table S2.…”
Section: Analysis Of Atomic Trajectories and X-ray Structuresmentioning
confidence: 99%
“…Before calculating S 2 XY , the protein trajectory structures are superimposed using the backbone atoms (N, C α , C) of residues 3-126 in the fit in order to eliminate the effect of overall rotation of the protein upon the S 2 XY -values. Use of only the backbone atoms of four of the five α-helices and two β-strands in [24][25][26][27][28][29][30][31][32][33][34][35][36][41][42][43][44][45][50][51][52][53][89][90][91][92][93][94][95][96][97][98][99][108][109][110][111][112][113][114][115] CD2 -values for Leu residues (Smith et al 2020).…”
Section: Analysis Of Atomic Trajectories and X-ray Structuresmentioning
confidence: 99%
See 1 more Smart Citation